(untitled) (Research, Society and Development, 2021)
The objective of this work was to carry out a phytosociological survey of weeds in the cultivation of cabbage in consortium with okra. The experiment was carried out in random blocks, with four replications. The treatments consisted of the following arrangements: T1 (three lines of cabbage with okra between the lines), T2 (three lines of cabbage with okra every two lines), T3 (three lines of cabbage with dense okra between the lines), T4 (three lines of cabbage with thick okra every two rows), T5 (cabbage), T6 (okra), T7 (thick okra) and T8 (oat straw). At 17 days after transplantation (DAT) and at fortnightly intervals up to 152 DAT, samples with 0.09 m2 were taken, randomly in each plot. Weeds were quantified and identified by establishing the total number of individuals and the total plant density per m². At the end of 77 and 152 DAT, absolute frequency, relative frequency, absolute density, relative density, absolute abundance, relative abundance and the importance value index of the most representative species were established. It was identified 23 species distributed in 14 families, highlighting the Asteraceae family, with 5 species. The most important species were Sonchus oleraceus and Richardia brasilenses, present in at least 5 of the 8 treatments. The T1 consortium had a reduction of 38% in the number of individuals and 37.9% in the density of plants per m² in relation to the cultivation of single cabbage. The consortium of cabbage with okra reduces weed infestation and can be explored as a management alternative.